Effects of metreleptin in patients with lipodystrophy with and without baseline concomitant medication use. (2nd November 2021) - Adamski, Kelly; Cook, Keziah; Gupta, Deepshekhar; Morris, Eric; Tuttle, Edward; Carr, Emma; Cremasco, Francesco; Cochran, Elaine; Brown, Rebecca J.
Abstract: Objective: To evaluate the effects of metreleptin in distinct subgroups of patients with generalized lipodystrophy (GL) and partial lipodystrophy (PL), using multivariate linear regression modeling to account for the role of patients' baseline usage of concomitant glucose and lipid-lowering medications and other covariates on their outcomes. Materials and methods: A post-hoc statistical analysis of two published single-arm, interventional, phase 2 clinical trials at NIH was conducted. Concomitant medication use was assessed for the clinical trial population using prescription fill data, measured at baseline and the post-one year following metreleptin initiation. Pre-specified co-primary efficacy endpoints measured were change from baseline in HbA1c at month 12, and the percent change from baseline in fasting serum triglycerides (TG) at month 12. Descriptive and statistical analyses were conducted for the overall population, the separate populations with GL and PL, and additional PL subgroups defined by baseline metabolic markers of elevated HbA1c and elevated fasting TG. Results: As previously reported, improvement in HbA1c and fasting TG from baseline to 12 months on metreleptin were observed in the overall population (mean change −1.57 percentage points and median change −37.9%, respectively) and subgroups. For both HbA1c and TG, baseline levels were significant predictors of changes after metreleptin. After considering baseline characteristics such as disease type, age, sex, and baseline HbA1c, baseline insulin use was not found to be a significant predictor of HbA1c improvement following metreleptin initiation. Similar results were seen for TG levels, with the use of any lipid-lowering medications at baseline not found to be a significant predictor of reductions in fasting TG levels. Conclusions: Patients treated with metreleptin experienced statistically significant improvement in metabolic markers of glycemic and hypertriglyceridemic control—e.g. HbA1c and triglyceride levels—across various subgroups after controlling for baseline characteristics and concomitant medication usage.